101 stupid things trainers do to sabotage success - Stern, Nancy (Richard Chang Associates IrvineUS, 1995)
Highlights 101 mistakes that trainers make. Explains the negative effects of the behaviours and suggests strategies for correcting them. Covers areas including: preparation of the training area; personal appearance and gestures; language, voice and expressions; methods and materials; preparation and use of equipment; and, time management.